Physiological Response of Three Varieties of Cayenne Pepper (Capsicum Frutescens) To Decreased Water Availability - Riyanto Sinaga (Talenta Publisher, 2020)
Physiological response of three chili pepper varieties on water availability has been examined. The objective of this research was to determine the response of three chili pepper varieties on decreasing water availability. This research used completely randomized factorial design with two variables, namely: three varieties of chili pepper (Local, Genie, and Baskhara) and five different percentages of water availabilities (10, 25, 50, 75, and 100%). that water availability had a significant effect on the decreasing of both shoot and root dry weight as well as on relative water content (RWC). Meanwhile, the decreasing water availability increased water use efficiency (WUE). The varieties of chili pepper showed a significant effect on shoot and root dry weight, shoot-root ratio, relative water content and on water use efficiency. The interaction of both variables showed a significant effect on water use efficiency as well as root dry weight.